2016
DOI: 10.15835/nsb819750
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Malarial Plants of Jonai, India: an Ethnobotanical Approach

Abstract: North-East India represents a unique ecosystem with treasured medicinal plant wealth closely related with Folk medicines. A large number of plants having medicinal properties and their folk uses have remained confined to the natives of this region. The tribal community of Jonai, Assam was explored to expose the indigenous herbal remedy for malaria. Sixteen antimalarial plants belonging to 13 families were reported. The analysis revealed highest fidelity level (FL) value for Ajuga integrifolia (100%) followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Lukhna biphang Bodo Whole plant Boiled in water to make a decoction and taken twice a day [39] Pakkom Jonai Tribe (Assam) Leaves [25] Orematong Karbi Tribe (Assam) Roots, leaves, and bark [39] Cough Tapen, Poto Adi, Nishi tribes (Arunachal Pradesh) Leaves Not specified [48] Antidote Umrem Naga Infusion of leaves mixed with bark Paste [50] Blood Purifier Puihnam Lushai tribe (Assam) Leaves Not specified [46] Toothache Oingtapo Galo tribe (Arunachal Pradesh)…”
Section: Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…Lukhna biphang Bodo Whole plant Boiled in water to make a decoction and taken twice a day [39] Pakkom Jonai Tribe (Assam) Leaves [25] Orematong Karbi Tribe (Assam) Roots, leaves, and bark [39] Cough Tapen, Poto Adi, Nishi tribes (Arunachal Pradesh) Leaves Not specified [48] Antidote Umrem Naga Infusion of leaves mixed with bark Paste [50] Blood Purifier Puihnam Lushai tribe (Assam) Leaves Not specified [46] Toothache Oingtapo Galo tribe (Arunachal Pradesh)…”
Section: Malariamentioning
confidence: 99%
“…There are also records of C. glandulosum being used against hepatic and gastric disorders in Manipur traditional medicine, as reported by Deb et al., 2015 [24] . C. glandulosum is used as an anti‐malarial plant as it was unveiled to be effective against the malarial parasite [25] . The Garo tribe of Meghalaya cooks C. glandulosum as a vegetable and uses it as a medicine for blood pressure [26] .…”
Section: Traditional Medicinal Usementioning
confidence: 99%
“…Fourteen different plant parts were used to treat diseases in the study. The most cited plant parts used in healthcare treatments are leaves (52 reports) followed by roots (11), fruits (10), rhizomes (9), barks (7), seeds (6), stems, flowers, shoots and aerial parts (5 each), peels (3), mucilage and whole parts (2 each) and latex (1) (Fig. 5).…”
Section: Fig 3: Life Forms (Plant Habits) Of Reported Medicinal Plant...mentioning
confidence: 99%
“…Due to the cultural and community diversity of the district, plant species are used in different diseases and purposes, such as religious practices 7,8 , anti-diabetic potential ethnobotanicals 9 , reproductive health 10 , anti-malarial treatment, etc. [11][12][13][14][15] . Besides medicinal plants in human healthcare, they are also used traditionally for ethnoveterinary purposes 16 .…”
mentioning
confidence: 99%
“…24,25 Ethnobotanical studies conducted in different parts of the world have revealed that A. integrifolia is utilized for the treatment of numerous conditions, including edema, febrile conditions, gout, rheumatism, amenorrhea, malaria, and diabetes. [26][27][28][29] In Ethiopian folk medicine, the plant is used for the treatment of diabetes, retained placenta, malaria, stomach ache, wounds, amoebiasis, cancer, diarrhea, liver problems, anthrax, hypertension, pneumonia, and epilepsy. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The plant parts used for the specified activities are the leaf, stem, and root.…”
Section: Introductionmentioning
confidence: 99%